TRENDS AND EVOLUTION OF PLASMA TECHNOLOGY FOR WASTEWATER TREATMENT FROM 2000 TO 2024: A SYSTEMATIC BIBLIOMETRIC ANALYSIS - Nurul Fadhilah Zayanah; Ganjar Samudro; Muhammad Nur; Asteria Marsha Firdausy; Ika Bagus Priyambada; Sarwoko Mangkoedihardjo; Azzah Nazihah Che Abdul Rahim (Universitas Trisakti, 2025)
The crisis in clean water availability due to population growth, industrialization, and climate change has driven the need for more effective and sustainable wastewater treatment technologies. Plasma technology is emerging as a potential solution capable of overcoming the limitations of conventional methods, especially in the degradation of complex pollutants and new polluting compounds. Aim: This study aimed to identify trends, developments, and research gaps related to the application of plasma technology in wastewater treatment during the period 2000-2024. Methodology and results: A bibliometric analysis was conducted to map the publication trends, most influential sources, and research networks, while qualitative content analysis was used to classify research themes and highlight key findings from the selected papers. One hundred sixty-five papers on plasma technology application in wastewater treatment were retrieved from four databases and analyzed. The results show that research in this field is categorized into four main themes: plasma-based pollutant degradation, plasma-enhanced oxidation processes, energy-efficient non-thermal plasma reactors, and dielectric barrier discharge (DBD) for environmental treatment. Furthermore, the research focus has shifted from basic plasma exploration to applying plasma technology for water treatment and efficiency improvement. Conclusion, significance and impact study: This study provides recommendations for future research based on the findings of current research trends and themes, aiming to guide the development of more effective and sustainable plasma-based wastewater treatment technologies.